Use of Geospatial, Hydrologic, and Geochemical Modeling to Determine the Influence of Wetland-Derived Organic Matter in Coastal Waters in Response to Extreme Weather Events - Rudolph, Jacob C.; Arendt, Carli A.; Hounshell, Alexandria G.; Paerl, Hans W.; Osburn, Christopher L. (Frontiers in Marine Science, 2020)
Flooding from extreme weather events (EWE), such as hurricanes, exports large amounts of dissolved organic matter (DOM) to both estuaries and coastal waters globally. Hydrologic connectivity of wetlands to adjacent river channels during flood events can potentially have a major control on the DOM exported to coastal waters after EWEs. In this study, a geographic information system based flood model was used to: (1) determine the volume of flooded wetlands in a river corridor following Hurricane Matthew in 2016; (2) compute the resulting volume fluxes of DOM to the Neuse River Estuary-Pamlico Sound (NRE-PS), in eastern North Carolina and (3) use the flood model to quantify the wetland contribution to DOM export. The flood model-derived contributions were validated with a Bayesian Monte Carlo mixing model combining measurements of DOM quality: specific UV Absorbance at 254 nm (SUVA254), spectral slope ratio (SR), and stable isotope ratios of dissolved organic carbon (δ13C-DOC). Results indicated that (1) hydrologic connectivity of the freshwater riparian wetlands caused the wetlands to become the primary source of organic matter (OM) that was exported into the NRE-PS after Matthew and (2) this source lingered in these coastal waters in the months after the storm. Thus, in consideration of the pulse-shunt concept, EWE such as Hurricane Matthew cause pulses of DOM from wetlands, which were the primary source of the OM shunted from the terrestrial environment to the estuary and sound. Wetlands constituted ca. 48% of the annual loading of DOC into the NRE and 16% of DOC loading into the PS over a period of 30 days after Hurricane Matthew. Results were consistent with prior studies in this system, and other coastal ecosystems, that attributed a high reactivity of DOM as the underlying reason for large CO2 releases following EWE. Adapting the pulse-shunt concept to estuaries requires the addition of a “processing” step to account for the DOM to CO2 dynamics, thus a new pulse-shunt process is proposed to incorporate coastal waters. Our results suggest that with increasing frequency and intensity of EWE, strengthening of the lateral transfer of DOM from land to ocean will occur and has the potential to greatly impact coastal carbon cycling.